Predictors of Second Language Acquisition in Latino Children With Specific Language Impairment - Gutiérrez-Clellen, Vera (2012)
PURPOSE: This study evaluated the extent to which the language of intervention, the child’s development in Spanish, and the effects of English vocabulary, use, proficiency, and exposure predict differences in the rates of acquisition of English in Latino children with specific language impairment (SLI). METHOD: In this randomized controlled trial, 188 Latino preschoolers with SLI participated in a small-group academic enrichment program for 12 weeks and were followed up 3 and 5 months later. Children were randomly assigned to either a bilingual or an English-only program. Predictors of English growth included measures of Spanish language skills and English vocabulary, use, proficiency, and exposure. Performance on English outcomes (i.e., picture description and narrative sample) was assessed over time. A series of longitudinal models were tested via multilevel modeling with baseline and posttreatment measures nested within child. RESULTS: Children demonstrated growth on the English outcomes over time. The language of intervention, Spanish skills, English vocabulary, and English use significantly predicted differences in rates of growth across children for specific measures of English development. CONCLUSIONS: This study underscores the role of the child’s first language skills, the child’s level of English vocabulary development, and level of English use for predicting differences in English acquisition in Latino preschoolers with SLI. These factors should be carefully considered in making clinical decisions.